Islamic Da'wah in Industrial Society: Study of PT Indorama Employees Synthetics Tbk Purwakarta - Zaenal Mukarom (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2020)
The employees of PT Indorama Synthetics Tbk Purwakarta as an industrial society have distinctive characteristic. The characteristics affect behavior and religious activities. This study aims to identify and reveal: (1) the Religious Behavior of PT Indorama Syntehtics Tbk Employees; (2) Da'wah Activities of PT Indorama Synthetics Tbk. Based on the results of the study found the following: (1) The religious behavior of industrial communities still tends to be normative and formalistic; (2) Da'wah activities in industrial communities are still temporal, momental, and ceremonial. There are two recommendations from the results of this study, namely: (1) There is a need to internalize religious values towards the industrial community; (2) There is a need for efforts to intensify da'wah for the industrial community.Karyawan PT Indorama Synthetics Tbk Purwakarta sebagai masyarakat industri mempunyai karakteristik yang khas. Karakteristik tersebut berpengaruh terhadap perilaku dan aktivitas keberagamaan. Studi ini bertujuan untuk mengetahui dan mengungkapkan: (1) Perilaku Keberagamaan Karyawan PT Indorama Syntehtics Tbk; (2) Aktivitas Dakwah Karyawan PT Indorama Synthetics Tbk. Berdasarkan hasil studi ditemukan beberapa hal berikut: (1) Perilaku keberagamaan masyarakat industri masih cenderung normatif dan formalistis; (2) Aktivitas dakwah masyarakat industri masih bersifat temporal, momental, dan seremonial. Ada dua rekomendasi dari hasil studi ini, yaitu: (1) Perlu adanya upaya internalisasi nilai-nilai agama terhadap masyarakat industri; (2) Perlu adanya upaya intensifikasi dakwah bagi masyarakat industri.